Exploration Ethnomatematics in Musical Instruments Gordang Nine with Theory Geometry Two Dimensions and Three Dimensions - Juni Sahfitri; Firmansyah; Dwi Novita Sari (International Journal of Educational Research Excellence (IJERE), 2022)
Draft mathematics used for explore existence mathematics in culture especially in art, one of which is in tools music gondang part time. one culture mandailing is Gordang Part time that is tool music traditionally composed from nine drums with different heights and diameters so that produce different tones and played by 5-6 players. Research this aim for knowing how history and concept mathematics contained in the musical instrument Gordang While. Obtained data form data qualitative whereas data source obtained from observation, documentation and related interview with godang musical instrument part time. Instrument in study this is guidelines interview, sheet observation, and documentation. Type study this is study qualitative character descriptive. Research results show that godang musical instrument Part time this born range 600 AD in the kingdom Sibaruar Connection. Nine drums of Gordang Part time have names different names on each area, consists of the 9 types of drums that have different sizes. Every size have 5 cm difference in each the drum. Gordang Part time have 1 type form geometry get up flat that is form circles on the top and bottom from tube Gordang Part time and 2 types form geometry get up room that is tube and cone beheaded.